Unmet needs in treating itch: reaching beyond eczema - Sarah G. Brooks; Gil Yosipovitch (Taylor & Francis Group, 2024)
Purpose Pruritus is an unpleasant sensation that creates the urge to scratch. In many chronic conditions, relentless pruritus and scratching perpetuates a vicious itch-scratch cycle. Uncontrolled itch can detrimentally affect quality of life and may lead to sleep disturbance, impaired concentration, financial burden, and psychological suffering. Recent strides have been made to develop guidelines and investigate new therapies to treat some of the most common severely pruritic conditions, however, a large group of diseases remains underrecognized and undertreated. The purpose of this article is to provide a comprehensive review of the challenges hindering the treatment of pruritus.Methods An online search was performed using PubMed, Web of Science, Google Scholar, and ClinicalTrials.gov from 1994 to 2024. Included studies were summarized and assessed for quality and relevance in treating pruritus.Results Several barriers to treating pruritus emerged, including variable presentation, objective measurement of itch, and identifying therapeutic targets. Itch associated with autoimmune conditions, connective tissue diseases, genodermatoses, cutaneous T-cell lymphoma, and pruritus of unknown origin were among the etiologies with the greatest unmet needs.Conclusion Treating pruritus poses many challenges and there are many itchy conditions that have no yet been addressed. There is an urgent need for large-scale controlled studies to investigate potential targets for these conditions and novel therapies.